Methods to Develop the Eye-tem Bank to Measure Ophthalmic Quality of Life. Issue 12 (December 2016) - Khadka, Jyoti; Fenwick, Eva; Lamoureux, Ecosse; Pesudovs, Konrad
ABSTRACT: Purpose: There is an increasing demand for high-standard, comprehensive, and reliable patient-reported outcome (PRO) instruments in all the disciplines of health care including in ophthalmology and optometry. Over the past two decades, a plethora of PRO instruments have been developed to assess the impact of eye diseases and their treatments. Despite this large number of instruments, significant shortcomings exist for the measurement of ophthalmic quality of life (QoL). Most PRO instruments are short-form instruments designed for clinical use, but this limits their content coverage often poorly targeting any study population other than that which they were developed for. Also, existing instruments are static paper and pencil based and unable to be updated easily leading to outdated and irrelevant item content. Scores obtained from different PRO instruments may not be directly comparable. These shortcomings can be addressed using item banking implemented with computer-adaptive testing (CAT). Therefore, we designed a multicenter project (The Eye-tem Bank project) to develop and validate such PROs to enable comprehensive measurement of ophthalmic QoL in eye diseases. Methods: Development of the Eye-tem Bank follows four phases: Phase I, Content Development; Phase II, Pilot Testing and Item Calibration; Phase III, Validation; and Phase IV, Evaluation. Conclusions/Discussion: This project will deliver technologically advanced comprehensive QoL PROs in the form of item banking implemented via a CAT system in eye diseases. Here, we present a detailed methodological framework of this project. Abstract : Supplemental digital content is available in the text.